The women reborn: A feminist revamping of Sleeping Beauty into Maleficient - Wafa Iqbal; Faheem Abbas; Sahar Iqbal (International Research Journal of Arabic and Islamic Studies, 2023)
Seeing a single side of a picture, voicing single view, constructing reality in your favor, generalizing your opinions universally, painting the world in mind as you want in short male norm is fading away. Now the world and word can be read from a subjective as opposed to exploiting and stereotypically oppressing male objective point of view. The text which was previously read as men (Culler, 2001) aping men to become anonymous and pseudonymous reader but now women have started ‘refusing to be stamped and stereotyped’ ( Woolf, 1929) and stop men from ‘exploitation and manipulation of female audience’( Showalter, 1941). This research studies ‘Maleficent’, a movie released in 2014, based on a famous Disney character of sleeping beauty. Woman who was ‘mythicized’ (Cixous, 1983) as horrifying and deadly creature is now ‘demythicized’ and ‘remythicized’ in the powerful and neglected constitution of Maleficent, story of each woman, a creature who places her faith in transforming power of love who can restore peace with her ‘true love kiss’ the power possessed by each woman. The aim of this paper is to symbolically read an apparently stereotypical story of gender actively and construct a positive interpretation of female characters specially the protagonist Maleficent.